Encapsulation and crystallisation behaviour inside carbon nanotubes and other fullerene-related structures - Sloan, J; Green, M; Hutchison, J; Tenne, R (1997)
The methods for preparing, opening and encapsulating materials inside carbon nanotubes are described. The crystallisation behaviour of materials inside carbon nanotubes, particularly with regard to the intimate mechanisms of morphological and orientational control of the carbon nanotube capillaries over crystallite growth are described and discussed. The encapsulation and crystallisation behaviour of catalytically incorporated species and that of materials incorporated inside inorganic fullerene-like structures are compared and contrasted with that observed inside nanotubes.